2021
DOI: 10.1080/10410236.2021.1880684
|View full text |Cite
|
Sign up to set email alerts
|

Health Beliefs, Trust in Media Sources, Health Literacy, and Preventive Behaviors among High-Risk Chinese for COVID-19

Abstract: The coronavirus disease (COVID-19) broke out in China in January 2020 and has been effectively controlled in April 2020 after China's relentless efforts. People's engagement in disease-related preventive behaviors is crucial in containing such infectious disease. Vulnerable populations often have higher chances of developing severe illness from COVID-19 and the mortality rate is also higher. Thus, at-risk populations for COVID-19 request extra attention. The current study conducted a national online survey amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 50 publications
4
40
0
Order By: Relevance
“…These findings were aligned with the existing literature, in which efficacies helped formulate protective actions and responses to the pandemic crisis (Rui et al, 2021). MSE (H4: β = 0.276, ρ < 0.05) and SSE (H5: β = 0.214, ρ < 0.05) showed a significant impact on the definition of health-protective behavior, which was in line with the existing pool of literature (Niu et al, 2021;Stosic et al, 2021;Wang et al, 2021). Furthermore, the benefits of being protected were observed to be significant in the overall model (H6: β = 0.133, ρ < 0.05), as suggested by Al-Sabbagh et al (2021) and Zampetakis and Melas (2021).…”
Section: Overall Modelsupporting
confidence: 87%
See 2 more Smart Citations
“…These findings were aligned with the existing literature, in which efficacies helped formulate protective actions and responses to the pandemic crisis (Rui et al, 2021). MSE (H4: β = 0.276, ρ < 0.05) and SSE (H5: β = 0.214, ρ < 0.05) showed a significant impact on the definition of health-protective behavior, which was in line with the existing pool of literature (Niu et al, 2021;Stosic et al, 2021;Wang et al, 2021). Furthermore, the benefits of being protected were observed to be significant in the overall model (H6: β = 0.133, ρ < 0.05), as suggested by Al-Sabbagh et al (2021) and Zampetakis and Melas (2021).…”
Section: Overall Modelsupporting
confidence: 87%
“…However, in recent decades, it became an integral part of HBM, as it holds a significant explanatory power to define public health concerns and protective behavior (Carico et al, 2020;Mirzaei-Alavijeh et al, 2020;Shahnazi et al, 2020;Tajeri et al, 2020). In existing HBM-based studies, self-efficacy was noted as a significant construct in exploring COVID19related behavioral research (Niu et al, 2021). Zhou et al (2020) suggested that correct news (information) could be an effective measure to control and reduce disease spread during the pandemic crisis, as self-efficacy enables individuals to seek valid and reliable health-related information in a more systematic fashion (Shang and Zuo, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The pandemic had spread rapidly across the country and had caused severe impact and harm to the production and life of the public. 5,6 On 20 January 2020, approved by the Chinese State Council and according to the prevention and control of infectious diseases of the People's Republic of China, the National Health Commission of China included COVID-19 into category B infectious disease and managed it in accordance with category A infectious diseases. 7 Category A infectious diseases are compulsorily managed infectious diseases, referred to as severe infectious diseases that are highly contagious and have a high case fatality rate, which are likely to cause pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…A higher level of health literacy, especially e-health literacy, is associated with COVID-19 awareness [8], positive attitudes towards preventive strategies against COVID-19 [9][10][11][12][13][14], and a higher adherence to prevention guidelines [8,15]. Health literacy is positively associated with COVID-19 vaccination acceptance [16] and can mitigate the negative effects of healthcare system distrust on vaccination willingness [17,18].…”
Section: Introductionmentioning
confidence: 99%